Fruits and Vegetables Moderate Lipid Cardiovascular Risk Factor in Hypertensive Patients - Bamidele Adewale Salau (BioMed Central, 2006)
Hyperlipidemia is a major risk factor in etiology of cardiovascular disease. Previous studies have shown association between vegetarian diet and low total serum cholesterol as well as LDL-cholesterol which is a pointer to low risk of cardiovascular disease. Dietary fiber, antioxidants and other classes of nutrients have been reported to ameliorate cardiovascular risk factors. Fruits and vegetables being rich sources of fiber and antioxidants have been the focus in intervention studies. The current work reports the effect local fruits and vegetables on cardiovascular risk factors in African hypertensive subjects in an 8 week study. Though there was no significant difference in the Body Mass Index and HDL-cholesterol at the end of the eighth week, there were significant reductions (P < 0.05) in serum triglycerides (125.87 ± 6.0 to108.27 ± 5.49 mgdL-1); total serum cholesterol (226.60 ± 6.15 to 179.20 ± 5.78) and LDL-cholesterol (135.69 ± 5.56 to 93.07 ± 7.18 mgdL-1). We concluded that consumption of combination of local fruits and vegetables may reduce the incidence of cardiovascular risk factors in Africans.